Undoing the sleights of hand: Prophets and scholars – two mythic discourses - Heever, Gerhard van den (HTS teologiese studies, 2007)
By comparing the historical recalibration of the myth of the Mother of the Gods in Athens with the scholarly construction of the mysteries in nineteenth and twentieth century religio-historical scholarship, this essay argues that just as primary practitioners of religious discourse engage in religious mythmaking, so too do scholars of religion. Both the practice of religion and scholarship on religion subsist in the political domain of social discourse and mythmaking. However, the two kinds of mythmaking are not simply identical. It is the distance to the discourse afforded the scholar that enables scholarship as politically committed denaturalisation, or historicisation, of religious tradition and reflexive scholarship. “Isn’t scholarship just another instance of ideology in narrative form? Don’t scholars tell stories to recalibrate a pecking order, putting themselves, their favorite theories, and their favorite people on top?” ... “Isn’t logos just a repackaged mythos?” ... to which I now respond: ‘If myth is ideology in narrative form, then scholarship is myth with footnotes.’” (Lincoln 1999:209)